Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Mineral-whole rock isotope fidelity? A comparative study of Hf-Nd-O from high Ba-Sr granitoids - E. Bruand; C. Storey; M. Fowler; B. Dhuime; R. Doucelance (Chemical Geology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fast analysis of caffeinated beverages using laser diode thermal desorption mass spectrometry (LDTD-MS/MS) - Wendy C. Andersen; Michael VanSickle; Joseph Storey; Virginia Sheldon; Jack Lohne; Sherri B. Turnipseed; Terri Thomas; Mark Madson (Food Additives & Contaminants: Part A, 2019)

Extended liquid chromatography high resolution mass spectrometry screening method for veterinary drug, pesticide and human pharmaceutical residues in aquaculture fish - Sherri B. Turnipseed; Joseph M. Storey; I-Lin Wu; Wendy C. Andersen; Mark R. Madson (Food Additives & Contaminants: Part A, 2019)

U–Pb isotopic dating of titanite microstructures: potential implications for the chronology and identification of large impact structures - K. Papapavlou; J. R. Darling; D. E. Moser; I. R. Barker; L. F. White; P. C. Lightfoot; C. D. Storey; J. Dunlop (Contributions to Mineralogy and Petrology, 2018)

Soil microbial community responses to contamination with silver, aluminium oxide and silicon dioxide nanoparticles - C. F. McGee; S. Storey; N. Clipson; E. Doyle (Ecotoxicology, 2017)

Zircon record of fractionation, hydrous partial melting and thermal gradients at different depths in oceanic crust (ODP Site 735B, South-West Indian Ocean) - A. Pietranik; C. Storey; J. Koepke; S. Lasalle (Contributions to Mineralogy and Petrology, 2017)

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Pollutant emissions and environmental assessment of ethyl 3-ethoxybutyrate, a potential renewable fuel - John M. E. Storey; Michael P. Bunce; Edwina M. Clarke; Jennifer W. Edmonds; Robert H. Findlay; Stephen M. C. Ritchie; Laurent Eyers; Zackery A. McMurry; James C. Smoot (Environmental Science and Pollution Research, 2016)

A rapid liquid chromatography determination of free formaldehyde in cod - Joseph M. Storey; Wendy C. Andersen; Andrea Heise; Sherri B. Turnipseed; Jack Lohne; Terri Thomas; Mark Madson (Food Additives & Contaminants: Part A, 2015)

Accuracy assessment of land surface temperature retrievals from Landsat 7 ETM + in the Dry Valleys of Antarctica using iButton temperature loggers and weather station data - Lars Brabyn; Peyman Zawar-Reza; Glen Stichbury; Craig Cary; Bryan Storey; Daniel C. Laughlin; Marwan Katurji (Environmental Monitoring and Assessment, 2014)

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

The regulation of AMPK signaling in a natural state of profound metabolic rate depression - Christopher J. Ramnanan; David C. McMullen; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Expression of Nrf2 and its downstream gene targets in hibernating 13-lined ground squirrels, Spermophilus tridecemlineatus - Pier Jr Morin; Zhouli Ni; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2008)

A multi‐scale segmentation approach to filling gaps in Landsat ETM+ SLC‐off images - S. K. Maxwell; G. L. Schmidt; J. C. Storey (International Journal of Remote Sensing, 2007)

The Canon of Potato Science - P. C. Struik; W. J. M. Lommen; A. J. Haverkort; R. M. J. Storey (Potato Research, 2007)

HIF-1α involvement in low temperature and anoxia survival by a freeze tolerant insect - Pier Morin; David C. McMullen; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2005)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Freezing survival, body ice content and blood composition of the freeze-tolerant European common lizard, Lacerta vivipara - Voituron Y.; Storey J.; Grenot C.; Storey K. (Journal of Comparative Physiology B, 2002)

Seasonal change and prolonged anoxia affect the kinetic properties of phosphofructokinase and pyruvate kinase in oysters - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 2000)

Activation of mitogen-activated protein kinases during natural freezing and thawing in the wood frog - Steven C. Greenway; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2000)

Discordant responses of mitogen-activated protein kinases to anoxia and freezing exposures in hatchling turtles - S. C. Greenway; K. B. Storey (Journal of Comparative Physiology B, 1999)

Suppression of reproductive development and longevity in the redshouldered leaf beetle,Monolepta australis (Col.: Chrysomelidae) by the tachinid,Monoleptophaga caldwelli (Dipt.) - H. A. C. Fay; R. I. Storey; S. G. Defaveri; J. D. Brown (BioControl, 1993)